Human monkeypox virus in the shadow of the COVID-19 pandemic - Almu'atasim Khamees; Sajeda Awadi; Khayry Al-Shami; Hayat Abu Alkhoun; Sharaf F. Al-Eitan; Ahmad Malek Alsheikh; Ahmad Saeed; Raed M. Al-Zoubi; Mazhar Salim Al Zoubi (Elsevier, 2023)
Background: The end of smallpox in 1980 and the subsequent stopping of vaccination against smallpox was followed by the emergence of monkeypox (mpox), a viral disease of animal origin, meaning that it is transmitted from animal to human. The symptoms of mpox are similar to smallpox, except that they are less severe in terms of clinical features. In the case of public health, the mpox virus is one of the most important orthopoxviruses (such as variola, cowpox, and vaccinia) that come from the family Poxviridae. Mpox occurs mostly in central Africa and sometimes in tropical rainforests or some urban areas. Also, there are threats other than COVID-19, that must be addressed and prevented from spreading, as there has been an outbreak of mpox cases since May 7, 2022, throughout the USA, Europe, Australia, and part of Africa. Objectives: In this review, we will discuss mpox between the past, the present and during the COVID-19 pandemic. Also, it offers an updated summary of the taxonomy, etiology, transmission, and epidemiology of mpox illness. In addition, the current review aims to highlight the importance of emerging pandemics in the same era such as mpox and COVID-19. Methods: A literature search was done for the study using online sources like PubMed and Google Scholar. Publications in English were included. Data for study variables were extracted. After the duplicate articles were eliminated, full-text screening was performed on the papers' titles and abstracts. Results: The evaluation included a series documenting mpox virus outbreaks, and both prospective and retrospectiveinvestigations. Conclusions: monkeypox is a viral disease caused by the monkeypox virus (MPXV), which is primarily found in central and western Africa. The disease is transmitted from animals to humans and presents symptoms similar to those of smallpox, including fever, headache, muscle aches, and a rash. Monkeypox can lead to complications such as secondary integument infection, bronchopneumonia, sepsis, and encephalitis, as well as corneal infection that can result in blindness. There is no specific clinically proven treatment for monkeypox, and treatment is primarily supportive. However, antiviral drugs and vaccines are available for cross-protection against the virus, and strict infection control measures and vaccination of close contacts of affected individuals can help prevent and control outbreaks.